Behavioral Effect of Oleoylethanolamide on Perinatal Asphyxia - Herrera, Maria Inés (2014)
Perinatal asphyxia (PA) is still a serious health problem associated with neuronal loss and morbidity. PA pathophysiology implies oxidative stress, cell damage and over activation of inflammatory response. The absence of an established treatment for PA encourages research on neuroprotective mechanisms. Oleoylethanolamide (OEA), a cannabinoid agonist that exerts anti-inflammatory actions through PPAR activation, could be a possible target for neuroprotection. However, its role in perinatal hypoxic brain injury remains still unknown. In this study, we evaluated the behavioral consequences of OEA treatment in 30 days-old asphyctic rats. Results indicated that rats subjected to OEA administration showed an improvement in exploratory locomotion. This data suggests a possible neuroprotective role of OEA in severe perinatal asphyxia modifications.